Community hospitals of the future—challenges and opportunities - Phang, Sean Kia Ann; Lin, Ming; Kho, Yong Xiang; Toh, Rui Jie Rachel; Kuah, Ting Ting; Lai, Yi Feng; Xie, JiaJing Kim (Frontiers in Health Services, 2023)
Background Medical training through specialisation has contributed significantly to clinical excellence in treating single acute conditions. However, complex patients' needs go beyond single diseases. There is a need to identify a group of generalists who are able to deliver cost effective, holistic care to patients with multiple co-morbidities and multi-faceted needs. Community Hospitals (CHs) are a critical part of Singapore’s shift towards a community-centric care model as the population ages. Community Hospitals of the Future (“CHoF”) represents a series of emerging conversations around approaches to reimagine and redesign care delivery in a CH setting in response to changing care needs. Methods An environmental scan in the CH landscape using semi-structured interviews was conducted with 26 senior management, management and working level staff from 7 Community Hospitals in Singapore. This environmental scan aims to understand the current barriers and future opportunities for CHs, to guide how CHs would have to shift in terms of (i) care delivery and resourcing, (ii) information flow, and (iii) financing, to conceptualize CHoF to meet the changing care needs in Singapore. Findings The analysis of all transcripts revealed four broad sections of themes, (i) current care delivery in CHs, (ii) current challenges of CHs, (iii) future opportunities and, (iv) challenges in reimagining CHs. An emerging theme regarding the current KPIs used also surfaced. Resource limitations and financing structure of CH surfaced as limitations to expanding its capability. However, room for expansion of CH roles tapping on the current expertise were acknowledged and shared. Conclusion With the current issues of (i) rapidly ageing population, (ii) specialist-centric healthcare system, and (iii) fragmentation of care eco-system, there is a need to further understand how CHoF can be modelled to better tackle them. Therefore several important questions have been devised to land us in a microscopic view on how to develop CHoF in the right constructs. Demographic changes, patient segmentation, service and regulatory parameters, patient’s perspective, care delivery, and financial levers (or lack of) are some of the categories that the interview questions looked into. Therefore, the data gathered would be used to guide and refine the concept of CHoF.